Analysis of the challenges of small-scale farmers’ access to labor in North Central Nigeria - Akintobi, O.S (Journal of Scientific Agriculture, 2020)
The study analyzed the challenges experienced by small-scale farmers’ in accessing human labour in North Central Nigeria. Multi-stage random sampling technique was used for sample selection while questionnaires were used for data collection. A total of 1,750 farmers were randomly interviewed. Data were analyzed using descriptive statistics and one-way factorial analysis of variance and mean separation was done at 5% probability level. Result revealed small scale farmers perceived a lack of access to human labour for agricultural activities in the zone while mean separation showed Niger state has the highest access to labour while Abuja and Kwara states are the least state with access to labour. High cost of labour, lack of fund and scarcity of labour are the major challenges experienced by the farmers in accessing labour for agricultural production. Based on the findings, the research concluded that small scale farmers do not good access to labour while facing serious challenges which has resulted into increased cost of production for the small-scale farmers. The study recommends among others that combine hiring should be encouraged among farmers for the adoption of expensive labour saving technologies/ implements.